Корреляция видов американских реалий и их соответствий в русском языке - Жукова, Л.К.; Рыжикова, М.Д. (Кримський науковий центр НАН України і МОН України, 2006)
The question about the correlation of the types of American realia and their correspondence in the Russian language is being raised for the first time. These are the realia that are the basis of the most cases of misunderstanding. The results of the investigation of the types of American realia and the ways of their correspondence are presented. The most widespread and informative types of the correspondence are translation loans and description.